Metabolic response of SH-SY5Y cells to gold nanoparticles by NMR-based metabolomics analyses. (27th July 2016) - Paris, Debora; Melck, Dominique; Longo, Angela; Napoletano, Sabrina; Carotenuto, Gianfranco; Nicolais, Luigi; Motta, Andrea; Vitale, Emilia
Abstract: Among various nanoparticles the gold derivatives (AuNPs) possess many features such as ease of synthesis at a tunable size, chemical stability and flexibility to undergo surface modifications, thus making them good candidates as bio-carrier across central nervous system and target diseased cells. However, a significant gap remains in data regarding their biosafety. We previously showed epigenetic modifications by short-term exposures of neuroblastoma SH-SY5Y cells to AuNPs conjugated with 2-mercapto-1-methylimidazole (AuNPs-mmi). Here, we investigated the effects of AuNPs-mmi on SH-SY5Y neuroblastoma cells through nuclear magnetic resonance-based metabolomics, to uncover the occurrence of perturbed pathways and deciphering possible phenotypic alterations. We found that AuNPs-mmi triggers a subtle and complex cellular response, which is initially characterized by cellular stress and toxicological reaction. In particular, we observed changes in catabolism of glucose, acetate and alanine, probably related to the energy-requiring endocytic process and oxidative stress. In addition, following nanoparticles' removal, alteration of acetate, choline, glutamine, glycine, tyrosine and leucine indicates a cellular reaction to stress and immune response. This effect was further confirmed by the production of metabolic endproducts such as glutamate, glycine and alanine. Moreover, the detected metabolites suggest a protective cellular response to the amounts of endogenous reactive oxygen species.